Business intelligence in higher education: Enhancing the teaching-learning process with a SRM system - Piedade, Maria Beatriz (2010)
Promoting students success requires the implementation of processes and mechanisms that allows the closely monitoring of the students academic activities. Although essential, the activities involved in this complex process do not take place in many higher education institutions due to the lack of appropriate practices and an adequate technological support that sustain these practices. To overcome this complex problem, a conceptual and a technological infrastructure was proposed and integrated into a Student Relationship Management (SRM) system. The SRM system is associated with Business Intelligence concepts and technologies used to obtain knowledge about the students and to support the decision making process. To validate the SRM system relevance, a set of applications cases were carried out in real contexts and supported by the implemented prototype. This paper presents some of the results obtained through the prototype implementation and on the analysis of the several actions that were carried out under the principles of the SRM practice.